2021
DOI: 10.1002/csr.2153
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of sustainable business models: Analysis from oil and gas industry

Abstract: The management of offshore platforms at the end of their production phase is a complex issue for technological, socioeconomic, ecological and safety reasons. The decommissioning or reconversion of offshore platforms in the context of a circular economy (CE) will lead to new knowledge acquisition, changing values and changing behaviours towards sustainability consistent with the 'new' business objectives. Multiuse platforms at sea (MUPSs) represent an interesting solution for development of marine infrastructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…(b) Key Partners: A network of reliable and efficient partners is crucial to minimize risks [104], especially in CRT. An extensive list of elements must be considered during the process of choosing strategic partners, such as linking to the value proposition, selection criteria, and developing a win-win relationship [105]. In this case study, the main network of members are rural entrepreneurs and other actors related to the CRT.…”
Section: Concept Development For Intelligent Digital Platforms In Crtmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Key Partners: A network of reliable and efficient partners is crucial to minimize risks [104], especially in CRT. An extensive list of elements must be considered during the process of choosing strategic partners, such as linking to the value proposition, selection criteria, and developing a win-win relationship [105]. In this case study, the main network of members are rural entrepreneurs and other actors related to the CRT.…”
Section: Concept Development For Intelligent Digital Platforms In Crtmentioning
confidence: 99%
“…(f) Channels: Elements that define how the product or service will reach the customer segment and convey the value propositions broadly and efficiently [104,105]. This research identified two main distribution channels for the case study, face-to-face and online.…”
Section: Concept Development For Intelligent Digital Platforms In Crtmentioning
confidence: 99%
“…Specifically, offshore platforms may be reused for several scopes such as marine research facilities, renewable energy systems, aquaculture farms or tourism points of interest (Chandler et al , 2017; Buck and Langan, 2017; Barile et al , 2017). In this direction, the new perspective of a sustainable decommissioning (Basile et al , 2021; Capobianco et al , 2021), based on the readaptation of these structures for sustainable aims, could bring several social benefits from an employment and local entrepreneurship perspective (Froehlich et al , 2017). However, the citizens’ perception regarding the future of the offshore platforms has not yet been extensively assessed, although the environmental and social impact of the decommissioning is growing and requiring a clear strategy on the government side.…”
Section: The Decommissioning Of Offshore Platforms (659)mentioning
confidence: 99%
“…According to BCG (Zeldovich, 2019), it was estimated that more than 50,000 offshore wells and 10,000 offshore structures will be decommissioned worldwide along with hundreds of thousands of onshore wells, facilities and sites. However, due to the decommissioning costs and environmental impacts of the complete removal, many operators are considering alternative uses of these assets by creating MUPs according to the value co-creation principles (Basile et al, 2021;Capobianco et al, 2021;Loia et al, 2021). Indeed, scholars have agreed that the reconversion of these platforms can deliver better environmental outcomes than the complete removal in terms of biodiversity enhancement, provision of reef habitat and protection from bottom trawling (Henrion et al, 2015;Lakhal et al, 2009).…”
Section: Decommissioning Offshore Platforms For Co-creating Valuementioning
confidence: 99%